Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1109/tns.2014.2304738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heavy Ion Irradiation on Perpendicular-Anisotropy CoFeB-MgO Magnetic Tunnel Junctions

Abstract: A non-volatile memory element called a perpendicular-anisotropy magnetic tunnel junction was fabricated using CoFeB/MgO/CoFeB film stack technology. It exhibits two stable resistance values, high or low, depending on the relative directions of the magnetizations of the two ferromagnetic CoFeB layers. After being programmed into the high resistance state with a current injection scheme based on the spin transfer torque theory, the tunnel junction was exposed to 15-MeV Si ions under different voltage stress cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
(25 reference statements)
0
26
0
Order By: Relevance
“…Damage and bit upsets induced by heavy ions were studied by Kobayashi et al [91], specifically investigating the effect of 15-MeV silicon atoms on the CoFeB/MgO/CoFeB pMTJ devices with a diameter of 70 nm and did not find resistance change. Later, the same group found that singleevent bit flips can occur in an MTJ cell resulting from heavyion exposure, depending on both the LET and properties of the bit [92].…”
Section: A Stt Magnetic Memorymentioning
confidence: 99%
“…Damage and bit upsets induced by heavy ions were studied by Kobayashi et al [91], specifically investigating the effect of 15-MeV silicon atoms on the CoFeB/MgO/CoFeB pMTJ devices with a diameter of 70 nm and did not find resistance change. Later, the same group found that singleevent bit flips can occur in an MTJ cell resulting from heavyion exposure, depending on both the LET and properties of the bit [92].…”
Section: A Stt Magnetic Memorymentioning
confidence: 99%
“…Particularly, the devices used in the aerospace are required to be radiation resistant to cosmic rays. Since MTJs are equipped with intrinsic magnetic immunity to radiation effect ( Kobayashi et al., 2014 ; Hughes et al., 2012 ; Ren et al., 2012 ; Park et al., 2019 ), MRAMs have already been used in satellites early in March 2008 ( Greenemeier, 2008 ). Moreover, featured with almost unlimited endurance, spin-orbitronic devices are particular favorable to be applied in avionics, e.g., a spacecraft, which may travel more than tens of years in the universe.…”
Section: Emerging Spin-orbitronic Devices Applicationsmentioning
confidence: 99%
“…Nevertheless, these effects will become more significant in electronic structures when the characteristic feature sizes will be reaching deeper into the nano-scale. Some studies tried to explain a posteriori the effects on MTJ irradiation sites by means of traditional LET cross-section plot or by exploiting TEM microscopy [4] [5]. In this paper, new insights are proposed to bring clear understanding on the possible basic degradation mechanisms that can trigger SEU in STT-MTJ, regardless of the radiation source, building a bridge between radiation effects and spintronic theory.…”
Section: Introductionmentioning
confidence: 99%